Imaji Borobudur sebagai Destinasi Pusat Religi Dunia melalui Media Digital - Latifah (UNISBA Press, 2023)
Abstract. One of the quickly expanding segments of the global tourist business is religious tourism. Religious destinations such as Borobudur in Indonesia have attracted tourists from around the world. Social media is become a crucial instrument. in promoting and representing the image of tourist destinations, including Borobudur, to a wider audience. This study is designed to analyze how the image of Borobudur as a central destination for world religion is represented through social media. This study utilizes a qualitative approach by analyzing digital media content related to Borobudur, such as photos, videos, and texts shared by social media users. Data is collected from major social media platforms. Through content analysis and descriptive analysis, the emerging image of Borobudur from social media will be identified and evaluated. The findings of this research provides insights into how social media represents the image of Borobudur as a central destination for world religion. Content analysis will reveal the most prominent visual and narrative elements in this representation, including depictions of architecture, religious ceremonies, and spiritual experiences at Borobudur. Additionally, this study will also identify the influence of digital media on netizens' perceptions and interest in Borobudur as a religious destination. This research has important implications for the development of religious tourism and destination marketing, particularly in optimizing the use of social media as a powerful tool for communication. The findings of this study can offer governments, tourism organizations, and other stakeholders useful advice to enhance the promotion and management of Borobudur as a central destination for world religion. Furthermore, this research can also serve as a foundation for further studies on digital media representation of religious destinations and the role of digital media in influencing tourists' perceptions. Abstrak. Pariwisata religi telah menjadi salah satu bidang pariwisata yang berkembang pesat di seluruh dunia. Destinasi religi seperti Borobudur di Indonesia telah menarik perhatian wisatawan dari seluruh dunia. Media sosial telah menjadi alat penting dalam mempromosikan dan merepresentasikan citra destinasi pariwisata, termasuk Borobudur, kepada khalayak umum. Studi ini bermaksud untuk mengkaji bagaimana citra Borobudur sebagai destinasi pusat religi dunia direpresentasikan melalui media digital. Studi ini menggunakan pendekatan kualitatif dengan menganalisis konten media sosial terkait Borobudur, seperti foto, video, dan teks yang dibagikan oleh pengguna media sosial. Data dikumpulkan dari platform media digital utama. Melalui analisis konten dan analisis deskriptif, citra Borobudur yang muncul dari media sosial akan diidentifikasi dan dievaluasi. Temuan penelitian ini memberikan wawasan tentang bagaimana media digital merepresentasikan citra Borobudur sebagai destinasi pusat religi dunia. Analisis konten akan mengungkapkan elemen visual dan naratif yang paling menonjol dalam representasi ini, termasuk penggambaran arsitektur, upacara keagamaan, dan pengalaman spiritual di Borobudur. Selain itu, studi ini juga akan mengidentifikasi pengaruh media sosial terhadap persepsi dan minat netizen terhadap Borobudur sebagai destinasi religi. Penelitian ini memiliki implikasi penting dalam pengembangan pariwisata religi dan pemasaran destinasi, terutama dalam mengoptimalkan peran media digital sebagai alat komunikasi yang efektif. Penelitian ini diharapkan dapat membantu pemerintah, organisasi pariwisata, dan pemangku kepentingan lainnya untuk meningkatkan promosi dan pengelolaan Borobudur sebagai destinasi pusat religi dunia. Selain itu, penelitian ini juga dapat berfungsi sebagai landasan untuk penelitian yang akan datang dalam hal representasi media digital tentang destinasi religi dan peran media digital dalam mempengaruhi persepsi wisatawan.